Training needs of staff and students in the use of software packages in selected Nigerian university libraries (2010)
The increasing pace of technological change necessitates the need for library staff and patrons to be properly trained in computer application. The study examined the extent of training programmes on the use of software packages in academic libraries. A total of 80 information professionals and 300 undergraduate students purposively selected from four academic libraries in South-West Nigeria constituted the population for the study. Data was collected using a structured questionnaire, interview and observations and analyzed using simple percentage calculation Findings of the study revealed that the core modules needed to operate on full automation were not available in some libraries. Also, most of the students were not exposed to training on the use of library software packages. Among the challenges associated with the training programmes were inadequate training facilities, poor attitude of staff to training and inadequate financial support. Training in the use of software is important for maximum use of the software for effective service provision. Library management should provide regular and consistent instruction to users, make available facilities for skills training to the staff and ensure adequate financial support for staff training and development.